Technology for preparing rare-earth tailings amelioration inocula by culturing plant growth-promoting bacteria with piggery wastewater as raw material - TIAN QIAOPENG; DOU XIN; LIAO XIANGRU; CAI YUJIE; GUAN ZHENGBING (2017)
The invention provides a technology for preparing rare-earth tailings amelioration inocula by culturing plant growth-promoting bacteria with piggery wastewater as a raw material. The technology is characterized in that the agricultural waste piggery wastewater is used as a raw material for culturing plant growth-promoting bacteria; and bacillus amyloliquefaciens H47 collected in the China Center for Type Culture Collection on June 24, 2013 with the collection No. of CCTCC M 2013283, commercial bacillus licheniformis and commercial Bacillus pumilus are used as the plant growth-promoting bacteria for preparation of the rare-earth tailings amelioration inocula. The piggery wastewater is used as the raw material for culturing the plant growth-promoting bacteria for preparation of the rare-earth tailings amelioration inocula. By the utilization of the plant growth-promoting bacteria for ammonium decomposition, soil fertility is increased. The product also can be used as a water-retaining agent, thus promoting form